Post-Roman Britain to Anglo-Saxon England - O'Brien, E; O'Brien, Elizabeth (1996)
﻿ This thesis is the result of a decision to extend the approach used by me when examining Irish burial practices, to a review of the archaeological and documentary record for burial practices and associated phenomena in the transitional period from late/post-Roman Britain to Anglo-Saxon England. The study considers burial rites; the method of disposal of physical remains, the position and orientation of bodies, and burial structures and enclosures: grave-goods are only referred to when they are pertinent to a particular line of argument. My intention is to draw together the various aspects of burial of the Iron Age, Romano-British and Anglo-Saxon periods in order to look at the overall picture. Occasionally this may mean stating the obvious, but by noting and plotting distributions of various burial traits first in the Iron Age and Romano-British periods, and then comparing these traits with the Anglo-Saxon period some revealing results can be obtained. It was important to begin with the Iron Age since some minority practices current in the early Anglo-Saxon period had a continuous history from the pre-Roman period. They are of importance in demonstrating the continuities that existed alongside major changes. [continued in text ...]